Alpha-Lipoic Acid: Biological Mechanisms and Health Benefits - Fabiana Superti; Rosario Russo (MDPI AG, 2024)
Alpha-lipoic acid (ALA) is a bioactive molecule with significant health effects. The biological action of ALA has been ascribed to the characteristic antioxidant properties of the oxidized form (ALA) and its reduced counterpart the dihydrolipoic acid (DHLA) system. The ALA/DHLA combination represents an ideal antioxidant since it can quench radicals, is able to chelate metals, is amphiphilic, and has no major adverse effects. This unique system is able to scavenge reactive oxygen species, exerting a major effect on tissue levels of reduced forms of other antioxidants, including glutathione. For this reason, ALA is also known as the "antioxidant of antioxidants". This review analyzes the antioxidant, anti-inflammatory, and neuroprotective effects of ALA and discusses its applications as an ameliorative tool for chronic diseases and those associated with oxidative stress. Results from in vitro and in vivo studies demonstrated that ALA modulates various oxidative stress pathways suggesting its application, alone or in combination with other functional substances, as a useful support in numerous conditions, in which the balance oxidant-antioxidant is disrupted, such as neurodegenerative disorders. Based on several successful clinical studies, it has been also established that oral ALA supplements are clinically useful in relieving the complications of diabetes and other disorders including cardiovascular diseases and nerve discomforts suggesting that ALA can be considered a useful approach to improving our health.